2004
DOI: 10.1021/jo049748g
|View full text |Cite
|
Sign up to set email alerts
|

Nitrile Ylide Dimerization:  Investigation of the Carbene Reactivity of Nitrile Ylides

Abstract: A series of novel hexaaryl diazatrienes 5 ("nitrile ylide dimers") were synthesized directly from the corresponding diaryl ketimines 12 and dichlorotoluenes 13 in a facile one-pot synthesis. The carbene character of the nitrile ylides was investigated by varying the substituents on the aromatic ring adjacent to the carbene center. The isolation of the corresponding carbene dimers as stable crystalline materials with absorption maxima (lambda(max)) from 363 to 422 nm was shown to be promoted by the absence of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 61 publications
1
19
0
1
Order By: Relevance
“…[10] In general, there are only a few examples known of the behaviour of nitrile ylides as imine-substituted carbenes, all of which are devoted to their dimerisation. [11] For example, the imine-stabilized carbene 16, which results from the thermolysis or photolysis of 4,5-dihydro-1,2,3λ 5 -dioxaphosphole (15), has been postulated as one of the intermediates in the formation of compound 19 (Scheme 6). [12] Scheme 5.…”
Section: Resultsmentioning
confidence: 99%
“…[10] In general, there are only a few examples known of the behaviour of nitrile ylides as imine-substituted carbenes, all of which are devoted to their dimerisation. [11] For example, the imine-stabilized carbene 16, which results from the thermolysis or photolysis of 4,5-dihydro-1,2,3λ 5 -dioxaphosphole (15), has been postulated as one of the intermediates in the formation of compound 19 (Scheme 6). [12] Scheme 5.…”
Section: Resultsmentioning
confidence: 99%
“…The resulting yellow slurry was stirred for 15 min, and the reaction mixture was treated with a mesitaldehyde 38 (2.1 g, 14 mmol) diluted with Et 2 O (10 mL). The temperature was kept below -85°C.…”
Section: Pyridino[43-c]-13-dihydro-1-hydroxy-3-mesityl[21]oxaborolmentioning
confidence: 99%
“…Several dimers were prepared and it was found that strong electron-withdrawing substituents suppressed the carbene-like reactivity of nitrile ylides [81]. Several dimers were prepared and it was found that strong electron-withdrawing substituents suppressed the carbene-like reactivity of nitrile ylides [81].…”
Section: Reactivity 41 Dimerizationmentioning
confidence: 99%